Didactical Design of Mathematical Communication Skill For Comparing And Sorting Of Fractions Concept By Contextual Teaching And Learning - Lestari, Agustin Puji (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
By preliminary studies on 5th grade of SDIT Buah Hati, namely grades 5A-5C still found learning barriers. To overcome this, the researchers compiled a didactic design that was implemented for students in grades 4A and 4B. The goal’s to reveal students' learning obstacles (LO) in comparing and sorting fractions. The research method used is Design Research and Didactical Design Research (DDR). Data collection techniques used learning obstacle tests, observation, interview, scale student opinion, and documentation The results of the implementation show that the design can overcome learning obstacles and improve students' mathematical communication skills, namely at the time of the preliminary study by 30% to 75% after the implementation of the initial design and by 92% after the design revision. The resulting didactic design can be used as an alternative in elementary school mathematics learning related to improving students' mathematical communication skills and the concept of comparing and sorting fractions.